2017
DOI: 10.3892/ol.2017.6073
|View full text |Cite
|
Sign up to set email alerts
|

Maslinic acid suppresses the growth of human gastric cells by inducing apoptosis via inhibition of the interleukin-6 mediated Janus kinase/signal transducer and activator of transcription 3 signaling pathway

Abstract: Abstract. The present study aimed to determine whether maslinic acid effectively inhibits the proliferation of MKN28 cells, and to investigate the mechanisms underlying its antitumor functions. MKN28 cell viability was evaluated using a Cell Counting Kit-8, cell proliferation was analyzed by a colony formation assay and flow cytometry was used to investigate the rate of apoptosis. Western blot analysis was performed in order to determine the differential expression levels of Janus kinase (JAK), signal transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
(35 reference statements)
0
15
0
Order By: Relevance
“… 33 , 34 IL-6 is one of the most prevalent cytokines that mediates its effects via the phosphorylation of STAT3. 35 In addition, Dominguez et al reported that intrathecal administration of IL-6 to naive rats rapidly activated microglial JAK/STAT3 and induced downstream changes that closely resemble controlled cortical impact (CCI)-evoked alterations. 36 Thus, we have reason to speculate the possible role of the P2Y 13 receptor in IL-6 production as well as the elevated activation of JAK2/STAT3 signaling in the development of DNP.…”
Section: Resultsmentioning
confidence: 99%
“… 33 , 34 IL-6 is one of the most prevalent cytokines that mediates its effects via the phosphorylation of STAT3. 35 In addition, Dominguez et al reported that intrathecal administration of IL-6 to naive rats rapidly activated microglial JAK/STAT3 and induced downstream changes that closely resemble controlled cortical impact (CCI)-evoked alterations. 36 Thus, we have reason to speculate the possible role of the P2Y 13 receptor in IL-6 production as well as the elevated activation of JAK2/STAT3 signaling in the development of DNP.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Akt may regulate apoptosis via modulation of Bcl‐2 family members (Zhang et al, ). The STAT3 signaling pathway is also a key anti‐apoptotic pathway in cancer cells because it is associated with cell proliferation, immune evasion, and apoptotic arrest (Liu et al, ; Wang, Tang, & Zhang, ). These effects are most likely mediated through ROS‐induced activation of the STAT3 pathway (Miao, Yu, Ren, & Yang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The STAT3 signaling pathway is also a key anti-apoptotic pathway in cancer cells because it is associated with cell proliferation, immune evasion, and apoptotic arrest (Liu et al, 2015;Wang, Tang, & Zhang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…MA (2‐α, 3‐β‐dihydroxyolean‐12‐en‐28‐oic acid, Figure a) is a pentacyclic triterpene acid widely distributed in dietary plants, especially abundant in olive fruit skins (Lozano‐Mena, Sanchez‐Gonzalez, Juan, & Planas, ). In the past years, MA has attracted much interest due to its proven pharmacological safety (Sanchez‐Gonzalez, Lozano‐Mena, Juan, Garcia‐Granados, & Planas, ), and various biological activities such as antitumor (Wang, Tang, & Zhang, ), antiinflammation (Fukumitsu, Villareal, Fujitsuka, Aida, & Isoda, ), antivirus (Mooi, Wahab, Lajis, & Ali, ), anti‐oxidation (Mkhwanazi, Serumula, Myburg, Van Heerden, & Musabayane, ), and antidiabetic activities(Guan et al, ). The cytotoxic activity of MA has been extensively studied in recent years.…”
Section: Introductionmentioning
confidence: 99%